2006
DOI: 10.1002/mats.200600023
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Diffusion Limitations in Bulk RAFT Polymerization

Abstract: Summary: The impact of diffusion limitations on RAFT polymerizations is investigated in this work. In particular, two models are compared: one accounting for diffusion limitations by using average chain lengths, the other accounting for the entire CLD. It is shown that such a description is necessary to correctly predict the kinetics of polymerization processes, as well as the evolution of average chain length and polydispersity. For properly selected study cases, differing conversion curves are obtained above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…It was also concluded that above 40% conversion different conversion curves could be obtained and at even higher conversions also different polydispersities. [166] …”
Section: àEmentioning
confidence: 97%
See 1 more Smart Citation
“…It was also concluded that above 40% conversion different conversion curves could be obtained and at even higher conversions also different polydispersities. [166] …”
Section: àEmentioning
confidence: 97%
“…Later, Peklak and Butté [166] examined the effect of diffusion limitations on RAFT polymerization using two approaches. They started from Equation (10) and considered either a chain-length-dependent diffusion coefficient of the macromolecules or a single, D p , depending on the number average degree of polymerization.…”
Section: A Case Study -Reversible Addition-fragmentation Transfer Polmentioning
confidence: 99%
“…Let us now look at terminations: the rates of these reactions are governed by the short chains of only a few monomer units length, as has been shown recently for nonliving emulsion polymerization systems43, 44 as well as for living systems 44. A comparison between the frequencies of propagation (π) and termination ( c ) inside particles containing two radicals under typical conditions of the experiments of this work shows that π/ c ≈ 1–2 (depending on the type of radical) and that a radical entering a particle will most likely only propagate one or two monomer units before terminating.…”
Section: Model Developmentmentioning
confidence: 97%
“…Most notably the observed termination reaction rate goes down, suppressing the loss of EGF and leading to an increase of the polymerization rate, i.e., a gel‐effect takes place. Next to that it is possible that also the RAFT exchange process is influenced by viscosity effects, specifically under highly polymer‐rich conditions for sufficiently high RAFT intrinsic addition and fragmentation reactivities . Several diffusion models have been developed to reflect the apparent RAFT exchange kinetics .…”
Section: Introductionmentioning
confidence: 99%
“…[37,38,41] Several diffusion models have been developed to reflect the apparent RAFT exchange kinetics. [37,38,41,42] It has been particularly shown that the control of dispersity is negatively affected upon strong diffusional limitations for the RAFT exchange process. Most kinetic studies on RAFT polymerization however ignore the impact of diffusional limitations in this exchange, leading to a biased interpretation of the RAFT polymerization kinetics and hampering the design and selection of optimal RAFT agents.…”
mentioning
confidence: 99%